A Community-Based Framework for Building Sustainable Tourism - Mallo, Erwin (Journal of Interdisciplinary Perspectives, 2025)
Exploring the community’s perspectives on sustainable tourism yields valuable and insightful ideas about their involvement in local tourism development. In terms of their development, which reflects the abundance of resources, manages economic benefits, fosters cultural openness to visitors, and promotes dynamic collaboration among stakeholders, this study employed a phenomenological research design to capture their experiences and perspectives on what it means to have sustainable tourism. Results show remarkable responses and themes that emphasize the factors contributing to promoting tourism in the province's various tourist attractions. The participants believed that sustainability in local tourism includes people in the form of security forces, community, private sectors, and LGUs; profit as a result of infrastructure development like roads and buildings, commercialization, investment in local tourism where investors gradually come in, and crop production they sold their local products and delicacies; a planet where it must be a safe and peaceful environment, maintenance and cleanliness, sustainable living and environmental conservation. Furthermore, a new aspect of tourism is the places themselves. As the participants believed, for tourism to become sustainable, it must be emphasized through government support, the absence of conflict, security, relaxation, and development. With these four domains — planet, profit, and places — sustainable tourism is described this way. This paper attempts to develop a new framework for creating sustainable local tourism.